Contagion through National and Regional Exposures to Foreign Banks during the Global Financial Crisis - Park, Cyn-Young; Shin, Kwanho (Journal of Financial Stability, 2020)
Although the global financial crisis of 2008 took root in advanced economies, its shocks spread through emerging economies, reflecting the increasingly interconnected global financial system. In this paper, we test the contagion effect at the country level using bilateral data on bank claims between countries. Direct and indirect exposures of emerging economies to crisis countries are empirically measured by using bilateral foreign claims from the Bank for International Settlements, and whether these exposures matter for capital outflows from emerging economies is tested. The findings show that emerging market economies more exposed to banks in the crisis-affected countries, both directly and/or indirectly, suffered more capital outflows during the global financial crisis. We also find that an emerging economy’s financial vulnerability can be influenced by its region’s overall exposure to crisis countries, indicating contagion effects at the regional level. Evidence also suggests that same-region lenders exhibited more favorable behavior toward the regional borrowers during the crisis, with important policy implications.